1983
DOI: 10.1007/bf00455734
|View full text |Cite
|
Sign up to set email alerts
|

The so-called atheromatous pseudoocclusion of the internal carotid artery

Abstract: The term "atheromatous pseudoocclusion" of the internal carotid artery (ICA) describes an extreme type of stenosing lesion which, during non-invasive procedure and conventional angiography is easily misdiagnosed as complete occlusion. Its recognition requires special sonographic and angiographic techniques. Nine subjects with pseudoocclusion could be observed during the last 12 months, most of them presenting minor strokes. Infarction suggesting a haemodynamic pathogenesis were demonstrated in seven of the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0
3

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 29 publications
2
30
0
3
Order By: Relevance
“…1,2,4,6,[9][10][11][12][13][14][15][16][17][18][19][20]28,31,45,[47][48][49][50][51]55,59,60,62,64,68,69,71,72 Pseudo-Occlusion. The term "pseudo-occlusion" was used for cases with raised intracranial pressure by Newton and Couch in 1960.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,4,6,[9][10][11][12][13][14][15][16][17][18][19][20]28,31,45,[47][48][49][50][51]55,59,60,62,64,68,69,71,72 Pseudo-Occlusion. The term "pseudo-occlusion" was used for cases with raised intracranial pressure by Newton and Couch in 1960.…”
Section: Figmentioning
confidence: 99%
“…Images from Sekhar et al can be called "near-occlusion with full collapse." "Pseudo-occlusion" has been used for the appearance of a collapsed artery, [1][2][3][4][5][6][7][8][9]11,[13][14][15][16][17][18][19][20][45][46][47][48][56][57][58][59][60][61][62][65][66][67][68][69][70] but also quite literally when diagnosis changed from occlusion to patent after re-review (not necessarily with distal collapse. 10,12,55,63,64,81 String Sign.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In 1983, Ringelstein et al 6 concluded that "immediate diagnostic clarification and emergency endarterectomy are mandatory" for near-occlusion with full collapse, diagnosed with low-flow findings on continuous-wave Doppler. However, this opinion was not an observed high risk of recurrent stroke but was based on that of 9 patients: Two had crescendo TIA at baseline, 2 had crescendo amaurosis fugax at baseline, and 2 rapidly progressed to occlusion.…”
mentioning
confidence: 99%
“…In fact, no risk of recurrent stroke was reported. 6 In 1989, O'Leary et al 7 reported that of 9 patients with near-occlusion (most likely with full collapse) who did not undergo carotid endarterectomy, 2 had an angiographic stroke and 3 had a recurrent ipsilateral stroke within 1 year. Presumably, the angiographic strokes affected further management.…”
mentioning
confidence: 99%